Small-scale synthesis of laboratory reagents with reaction modeling - Lerner, Leonid (Boca Raton : CRC Press, 2011)
'The in-lab preparation of some chemical reagents provides a number of advantages over purchasing commercially-prepared samples. This volume contains a detailed description of methods for the rapid and reliable synthesis of many useful reagants that are otherwise difficult to obtain. It provides spectroscopic analyses of products, presents the thermodynamic/kinetic data of reactions, and offers a thorough analysis of the purity of the final products. Enhanced by useful diagrams and photographs, this text is a valuable reference for researchers in small or remote laboratories'--
'When working in a small chemical laboratory attached to a non-chemistry specific project one is frequently asked to solve problems which occur in the main project. Usually one can think of several solutions and experimental testing is required to choose between the different approaches, or indeed to find an approach that works. These often require the use of small amounts of chemicals which the laboratory does not stock. Obtaining these chemicals from commercial suppliers in a suitable timeframe sometimes poses problems. This is particularly the case in isolated regions such as Australasia, when the supplier has no local stocks of hazardous substances and they have to be brought in from overseas, something which can introduce delays from several weeks to six months or more. Since there is no certainty that the substance whose acquisition is introducing the delay will form part of the ultimate solution, this delay is particularly objectionable. The primary aim of this book is therefore to provide reliable laboratory syntheses of the most common reagents whose acquisition can introduce delays due to their hazardous nature. It is apparent that there is little point in replacing delays in reagent purchase with uncertainties in their synthesis, hence the preparations presented in this book were chosen with the following criteria in mind: short duration, availability of apparatus, high yield, and high purity of the product. It was also considered necessary for the syntheses to be described in greater detail than is normally provided in the literature, since I have frequently found that omission of apparently small details can subsequently waste much time'--
Includes bibliographical references and index.
Keywords: Chemical tests and reagents -- Synthesis